Efficacy of Head Rotation Exercises in Dysphagic Patients: Speech and Language Pathologist Perspective - Zulfiqar, Nimra; Ahmed, Muhammad; Tahira, Sadia; Yaqoob, Saba; Maqsood, Hiba; Shafique, Sibgha (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
Background: The transportation of food from oral cavity to stomach done by various processes which is called Normal Swallowing process. Abnormality occurs in normal processes defined as Dysphagia. Several methods are used to compensate this issue including various compensatory techniques and exercises. Head rotation exercises is one of this compensatory strategy. Objective: The objective of the present study was to determine the Efficacy of Head Rotation exercises in Dysphagic patients: SLP Perspective Materials & Methods:A Self designed questionnaire was used as data collecting instrument after the approval of the synopsis. This questionnaire was designed with the help of expert opinion and Literature review by using Delphi technique. 50 speech and language therapists filled the questionnaire, and data were then analyzed using standard SPSS Software. Results: According to concluded data, 72% Speech Therapists were agreed that Head rotation exercises proves beneficial and very effective for the treatment of dysphagic patients. Conclusion: It is concluded that Head rotation exercises are effective in treating dysphagic patients. Thereby, improving swallowing to almost normal previous state.